Insolvency Issues in the Covid Period - Simona Petrina GAVRILA; Florin TUDOR; Andreea Elena MATIC (Communications of International Proceedings, 2021)
The declared purpose of the insolvency, as regulated by law no. 85/2014 is the establishment of a collective procedure to cover the debtor's liabilities, "with the granting, when possible, of the chance to recover his activity". The analysis of this legal provision, as well as of all the rules governing insolvency, shows that the Romanian legislator complies with the European Commission Recommendation of 12.03.2014 on a new approach to business failure and insolvency, to ensure that viable businesses facing financial difficulties (...) have access to national insolvency frameworks that allow them to restructure their activity at an early stage, in order to prevent their insolvency and, therefore, to maximize the total value for creditors, employees, owners and economy as a whole, respectively to give a second chance to insolvent debtors, the opening of bankruptcy proceedings needing to be started only after the exhaustion of solutions that allow reorganization. But what happens to these debtors, who are trying to recover their activity, in conditions of economic and judicial blockade, such as those caused by the COVID 19 pandemic, which the whole world has faced since the first months of 2020. The Romanian legislator has taken a series of economic, fiscal and commercial measures, likely to protect traders from the harmful effects of the pandemic, some of which also apply to insolvent debtors. The purpose of this study is to identify these legislative measures and to analyze their impact on the activity of insolvent debtors, respectively on their chances of economic recovery.
Keywords: Insolvency; Judicial Reorganization; Covid pandemic; Legislative Measures; fiscal impact; Romania